2019 IEEE/CVF International Conference on Computer Vision (ICCV) 2019
DOI: 10.1109/iccv.2019.00076
|View full text |Cite
|
Sign up to set email alerts
|

Robust Motion Segmentation From Pairwise Matches

Abstract: In this paper we address a classification problem that has not been considered before, namely motion segmentation given pairwise matches only. Our contribution to this unexplored task is a novel formulation of motion segmentation as a two-step process. First, motion segmentation is performed on image pairs independently. Secondly, we combine independent pairwise segmentation results in a robust way into the final globally consistent segmentation. Our approach is inspired by the success of averaging methods. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(45 citation statements)
references
References 61 publications
(146 reference statements)
0
45
0
Order By: Relevance
“…In [3] it is observed that all the two-frame segmentations involving a fixed image provide -up to a permutation of the motions -a possible solution for clustering points in that image. In order to resolve such ambiguity, permutation synchronization [31] is performed.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…In [3] it is observed that all the two-frame segmentations involving a fixed image provide -up to a permutation of the motions -a possible solution for clustering points in that image. In order to resolve such ambiguity, permutation synchronization [31] is performed.…”
Section: Related Workmentioning
confidence: 99%
“…They belong to the second category (i.e., the case of two-frame correspondences represented in the middle of Fig. 1) and are inspired by [3]. The first approach -named TriSeg-addresses motion segmentation in two steps:…”
Section: Contributionmentioning
confidence: 99%
See 3 more Smart Citations